(untitled) - Schaffer, Kay (New York, 2004)
Personal narratives have become one of the most potent vehicles for advancing human rights claims across the world.Human Rights and Narrated Livesexplores what happens when autobiographical narratives are produced, received, and circulated in the field of human rights. It asks how personal narratives emerge in local settings; how international rights discourse enables and constrains individual and collective subjectivities in narration; how personal narratives circulate and take on new meanings in new contexts; and how and under what conditions they feed into, affect, and are affected by the reorganization of politics in post-cold war, postcolonial, globalizing human rights contexts.
Keywords: Human rights